Analysis of the Morphology and Lithology of the Kisangani–Yangambi Section of the Congo River in the Democratic Republic of Congo - Mawa Mukulia, Prométhée; Katembo Kasekete, Désiré; Makabu Kayembe, Gabriel; Muhindo Sahani, Walere; Kahindo Muhongya, Jean-Marie (Modern Geográfia, 2024)
The Congo River, which is between 900 and 300 metres wide between the city of Kisangani and the town of Yangambi, is characterised by important socio-economic and conservation activities but also by a lack of knowledge on morphological and lithological matters. To fill the gaps, the lithology and the morphological dynamics of the riverbed were studied through a description of islands (between 1984 and 2017) and banks thanks to remote sensing and field work, respectively. With regard to the number of islands, the study revealed a loss of 5.13% and a recovery of 28.21% between 1984 and 2017. The direct factors of this dynamism are the erosion and landslides observed both on the banks and on the islands. The geological survey method allowed the collection of 4 samples of sound indurated rocks and 50 samples of loose rocks on the soil profiles of the islands and banks. The macroscopic description and sieving of the samples with 63 mm and 2 mm mesh size allowed the lithology map to be drawn up. The fine soil particles were analysed in the soil laboratory using the Robinson–Köhn pipette method to determine their texture. The USDA textural classification was used. The results of the analysis showed that sand is the predominant rock element in the area. Such a lithology would increase the sensitivity of the banks to mass movements observed here and there along the Kisangani–Yangambi river section.